PENGARUH PERAN KELEMBAGAAN LOKAL ADAT TERHADAP PEMBANGUNAN INFRASTRUKTUR DESA KOTO MUDIK KECAMATAN AIR HANGAT BARAT KABUPATEN KERINCI: EKA SEPTIANI, S.Sos., M.Si - Eka Septiani (LPPM STIA Nusantara Sakti, 2018)
This study aims to determine the effect, the influence of the role of Indigenous Local Institutions on the Infrastructure Development of Koto Mudik Village, Kecamatan Air Hangat Barat, Kabupaten Kerinci. The formulation of the problem posed is: Is there an Influence of the Role of Indigenous Local Institutions on Village Infrastructure Development? How Big is the Influence of the Role of Indigenous Local Institutions on Village Infrastructure Development ?. The influence of the role of local customary institutions on village infrastructure development must be seen based on indicators of the role of local customary institutions on village infrastructure development, and the data analysis technique used is simple linear regression. Based on data analysis, it is known that the coefficient of influence of the role of Indigenous Local Institutions on Village Infrastructure Development is 39,6%. Then it was discovered that the influence of the role of the Local Customary Institutions on Infrastructure Development was 28,5%. Furthermore, the results of the study where the value of t arithmetic of 2,940 (sig 5%) = 0. 176 or t arithmetic 2,940 > t table 2.831, meaning that Ho is rejected Ha accepted, which means the role of Indigenous Local Institution has a significant effect on Infrastructure Development in Koto Mudik Village.